Perceived Talent Management and Turnover Intention: Mediating Role of Career Adaptability - Abdullah Khalfan Alrushadi; Kamisah Supian; Nor Azah Jahari (STIE Malangkucecwara, 2026)
This paper presents a conceptual framework that investigates the potential mediating role of career adaptability in the relationship between perceived talent management practices and employee turnover intention. The proposed conceptual model is grounded in self-determination theory (SDT) and career construction theory (CCT). It incorporates three core dimensions of talent management namely, talent attraction, talent development, and talent retention alongside the psychological construct of career adaptability, which includes concern, control, and confidence. These elements are integrated to explore how talent management practices influence turnover intention through motivation and adaptive career behaviours. The framework was developed through an integrative review of empirical studies published between 2015 and 2025. Being conceptual in nature, the model awaits empirical testing. For human resource professionals, this study offers valuable insights into how fostering career adaptability can support talent retention efforts in today’s dynamic work environments. The study contributes to the growing literature by examining less-explored psychological pathways linking perceived talent management practices and turnover intention, with a contextual emphasis on emerging markets.